Author Correction: P53 and mTOR signalling determine fitness selection through cell competition during early mouse embryonic development - Sarah Bowling (Nature Portfolio, 2018)
The original version of this article contained an error in the spelling of Juan Pedro Martinez-Barbera, which was incorrectly given as Juan Pedro Martinez Barbera. This error has now been corrected in both the PDF and HTML versions of the Article.